Medial prefrontal cortex serotonin 1A and 2A receptor binding interacts to predict threat-related amygdala reactivity - Fisher, Patrick M (BioMed Central, 2011)
BACKGROUND: The amygdala and medial prefrontal cortex (mPFC) comprise a key corticolimbic circuit that helps shape individual differences in sensitivity to threat and the related risk for psychopathology. Although serotonin (5-HT) is known to be a key modulator of this circuit, the specific receptors mediating this modulation are unclear. The colocalization of 5-HT(1A )and 5-HT(2A )receptors on mPFC glutamatergic neurons suggests that their functional interactions may mediate 5-HT effects on this circuit through top-down regulation of amygdala reactivity. Using a multimodal neuroimaging strategy in 39 healthy volunteers, we determined whether threat-related amygdala reactivity, assessed with blood oxygen level-dependent functional magnetic resonance imaging, was significantly predicted by the interaction between mPFC 5-HT(1A )and 5-HT(2A )receptor levels, assessed by positron emission tomography. RESULTS: 5-HT(1A )binding in the mPFC significantly moderated an inverse correlation between mPFC 5-HT(2A )binding and threat-related amygdala reactivity. Specifically, mPFC 5-HT(2A )binding was significantly inversely correlated with amygdala reactivity only when mPFC 5-HT(1A )binding was relatively low. CONCLUSIONS: Our findings provide evidence that 5-HT(1A )and 5-HT(2A )receptors interact to shape serotonergic modulation of a functional circuit between the amygdala and mPFC. The effect of the interaction between mPFC 5-HT(1A )and 5-HT(2A )binding and amygdala reactivity is consistent with the colocalization of these receptors on glutamatergic neurons in the mPFC.